CICLO ANUAL DE RIBAUTIANA TENERRIMA (HERRICH-SCHAFFER, 1834) (HEMIPTERA: CICADELLIDAE) EN EL SUR DE CHILE - Carrillo, R.; Neira, M.; Ríos, L.; Cifuentes, C. (Acta Entomológica Chilena, 2022)
Ribautiana tenerrima (Herrich-Schaffer, 1834) behaved as a bivoltine species in Southern Chile. Overwintering occurs at the egg stage inside leaf tissue of Rubus constrictus and perhaps of other Rubus species. Eggs in host plants lossing their leaves during winter time were unable to survive.